Vascularized composite allotransplantation: current standards and novel approaches to prevent acute rejection and chronic allograft deterioration. (14th September 2015) - Kueckelhaus, Maximilian; Fischer, Sebastian; Seyda, Midas; Bueno, Ericka M.; Aycart, Mario A.; Alhefzi, Muayyad; ElKhal, Abdallah; Pomahac, Bohdan; Tullius, Stefan G.
Summary: The advent of more potent immunosuppressants led to the first successful human upper extremity transplantation in 1998. At this time, >100 upper extremity transplants, 30 face transplants, and a variety of other vascularized composite allotransplantation (VCA) procedures have been performed around the world. VCA recipients present unique challenges for transplantation. The incidence of acute rejection exceeds 80% in hand and face transplantation and is well documented, whereas reports about antibody‐mediated rejection and chronic rejection remain scarce. Immunosuppression protocols commonly used at US centers are derived from solid organ transplantation protocols. Novel approaches to minimize rejections in VCA may include improved HLA matching and considerations toward cytomegalovirus infection status. New graft preservation techniques may decrease immunogenicity prior to transplant. Novel monitoring methods such as valid biomarkers, ultrasound biomicroscopy, and sentinel flaps may enable earlier diagnosis of rejection. Cell‐based therapies are being explored to achieve immunosuppressive regimen minimization or even tolerance induction. The efficacy of local immunosuppression in clinical VCA remains controversial. In conclusion, although immunosuppressive strategies adapted from SOT have demonstrated good midterm results, focusing on the unique features of VCA grafts may enable additional, more specific treatment strategies in the future and improved long‐term graft outcomes.